The Hills Have Eyes II - Aja, Alexandre, 1978-; Dan, Byrd.; Emilie de Ravin; Kathleen Quinlan; Michael Bailey Smith; Ted Levine; Tom Bower; Maxime Giffard (USA Craven-Maddalena Films, 2006)
Wes Craven produces this remake of his 1977 classic of the same name, about the Carters, an idyllic American family travelling through the great American southwest. But their trip takes a detour into an area closed off from the public, but more importantly from society. An area originally used by the U.S. Government for nuclear testing that was intended to be empty...or so they thought? When the Carter's car breaks down at the old site, they're stranded...or are they? As the Carters may soon realize that what seemed like a car casually breaking down, might actually be a trap. This trap might be perpetrated by the inhabitants of the site who aren't pulling a prank, but are out to set up a gruesome massacre.
A suburban American family is being stalked by a group of psychotic people who live in the desert, far away from civilization.
Wes Craven
Languages: English Subtitles: No Subtitles
Keywords: Thriller; Horror